1996
DOI: 10.1046/j.1365-2249.1996.41749.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a soluble form of CD58 in synovial fluid of patients with rheumatoid arthritis (RA)

Abstract: SUMMARYReduced levels of a soluble form of the adhesion receptor and CD2 ligand CD58 (sCD58) were previously described in RA patients. In order to understand the biological significance of this finding we biochemically characterized sCD58 in RA and asked how well sCD58 binds to CD2. sCD58 concentrations were measured in serum and synovial fluid (SF) samples of RA patients by two ELISAs, one detecting domain 1 of CD58 (CD58-D1), and the other one the complete molecule (CD58-D1 D2). Small amounts of split sCD58-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The CD2/CD58 binding is involved in most T-cell interactions with the other cells and in T-cell activation. Moreover, the binding of CD2/CD58 has significant importance in autoimmune diseases such as RA because it plays a crucial role in lymphocyte recruitment to the inflammatory sites [ 101 , 102 ]. The levels of soluble form of CD58 (sCD58) were found to be significantly reduced in sera and synovial fluid of RA patients in relation to healthy donors and patients with SpA.…”
Section: Chondrocyte Antigens As Potential Targets In Inflammatory Jomentioning
confidence: 99%
“…The CD2/CD58 binding is involved in most T-cell interactions with the other cells and in T-cell activation. Moreover, the binding of CD2/CD58 has significant importance in autoimmune diseases such as RA because it plays a crucial role in lymphocyte recruitment to the inflammatory sites [ 101 , 102 ]. The levels of soluble form of CD58 (sCD58) were found to be significantly reduced in sera and synovial fluid of RA patients in relation to healthy donors and patients with SpA.…”
Section: Chondrocyte Antigens As Potential Targets In Inflammatory Jomentioning
confidence: 99%
“…A recent study has shown an association between the high expression of CD2/CD58 molecules and RA . CD58 expression is known to be upregulated in inflammatory lesions; this leads to targeted recruitment of T cells into inflammatory sites . CD58 is widely distributed among cell types of the synovial microenvironment and provides numerous cell types with which lymphocytes can interact via CD2 molecule.…”
mentioning
confidence: 99%
“…Hoffmann et al, have reported that serum and synovial fluid sCD58 levels in patients with RA were found reduced compared to the levels in normal controls and patients with osteoarthritis (OA) or spondylarthropathy (SpA) [49]. Since soluble CD58 (sCD58) may normally mediate de-adhesion, decreased albumin concentrations due to systemic inflammation may lead to reduced sCD58 levels, thus resulting in increased T cell adhesiveness.…”
Section: Cd2 and Cd58 Roles In Disease Pathologymentioning
confidence: 99%
“…Insufficient release of sCD58, e.g. in synovitis, might result in T cell accumulation and perpetuation of inflammation [49]. In addition, endothelial cells in RA have been shown to express elevated levels of CD58 and in SF, RA lymphocyte expresses increased levels of CD2 and CD58 [50] relative to RA or normal PB lymphocytes.…”
Section: Cd2 and Cd58 Roles In Disease Pathologymentioning
confidence: 99%